POVERTY PROBABILITY OF AGRICULTURAL WORKERS IN SOUTH KALIMANTAN - Rachman F.F.; Yanti N.D.; Fauzi M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The agricultural sector is the main sector with the third largest share of GRDP in South Kalimantan after mining and electricity and gas procurement in 2021. Meanwhile, the poverty rate in South Kalimantan in the same year is ranked as the third province with the lowest poverty rate in Indonesia. In line with the mandate of the President of the Republic of Indonesia regarding the eradication of extreme poverty in 2024, a strategy for reducing chronic poverty and accelerating poverty alleviation is needed. Therefore, a picture of poverty is needed, especially for groups of people who are considered vulnerable, such as agricultural sector workers so that the South Kalimantan Provincial Government can formulate appropriate policies to realize this mandate. This study aims to analyze the conditions, percentages, characteristics, and poverty probabilities of the working poor in the agricultural sector in South Kalimantan. The research data used is secondary data obtained from the March 2021 National Socioeconomic Survey (Susenas) which is matched with the 2021 Village Potential Data Collection (Podes) data. The analytical method used in this research is binary logistic regression. The results showed that the variables that had a significant influence on the poverty status of agricultural sector workers in South Kalimantan were area classification, number of household members, education, network, the existence of Bumdes and kiosks/shops for agricultural production facilities in the village/municipality.